2013
DOI: 10.1016/j.envsoft.2013.03.015
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of carbon accounting tools for arable crops in the United Kingdom

Abstract: NOTICE: this is the author's version of a work that was accepted for publication in Environmental Modelling & Software. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Environmental Modelling & Software, vol 46, 2013, DOI 10.1016/j.envsoft.20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 23 publications
(39 reference statements)
0
49
0
3
Order By: Relevance
“…[46], which compared this tool with ten other GHG calculators for either single crops or for whole farms (CALM, C-PLAN, CCalc, Organic Farmer Carbon calculator, Muntons barley calculator, Biograce calculator, RFA e RTFO Carbon Calculator, BEATv2, RSB Tool, HGCA Biofuel GHG Calculator) using multi-criteria decision-making methods, and it was concluded that the Cool Farm Tool was the highest-rated tool recommended for single crop assessments like the case study of this work.…”
Section: Product Carbon Footprint (Pcf)mentioning
confidence: 99%
“…[46], which compared this tool with ten other GHG calculators for either single crops or for whole farms (CALM, C-PLAN, CCalc, Organic Farmer Carbon calculator, Muntons barley calculator, Biograce calculator, RFA e RTFO Carbon Calculator, BEATv2, RSB Tool, HGCA Biofuel GHG Calculator) using multi-criteria decision-making methods, and it was concluded that the Cool Farm Tool was the highest-rated tool recommended for single crop assessments like the case study of this work.…”
Section: Product Carbon Footprint (Pcf)mentioning
confidence: 99%
“…These tools vary in how they account for GHG emissions from the various activities involved in agriculture. There is consensus however around the fact that such tools do provide a way to "educate" farmers about sources of emissions and climate change generally, and can serve to facilitate more transparent information sharing between the parties involved in agricultural products chains (Whittaker et al, 2013).…”
Section: Carbon Reduction In Food Supply Network: Between Control Anmentioning
confidence: 99%
“…Over the last decade, a number of LCA-based carbon reporting tools have been developed in the agricultural sector, particularly in the United Kingdom (UK) (Whittaker et al, 2013). These tools vary in how they account for GHG emissions from the various activities involved in agriculture.…”
Section: Carbon Reduction In Food Supply Network: Between Control Anmentioning
confidence: 99%
“…Whittaker, McManus and Smith (2013) argue the significance of their study by emphasizing the fact that, of all economic sectors in the UK, agriculture contributes with around 9% of GHG emissions annually, and is a significant component of the lifecycle emissions of many everyday food and other products. In a similar fashion, O'Brien et al (2014) compare the effect of applying two different methods when completing a marginal abatement cost curve analysis of national agricultural GHG emissions.…”
Section: Introductionmentioning
confidence: 99%